The New Dollars and Dreams : American Incomes in the Late 1990s - Levy, Frank, 1941- (Book collections on Project MUSE., 1998)
The New Dollars and Dreams explores today's puzzling economic landscape, in which low unemployment goes hand in hand with sluggish wage growth and high income inequality. This book offers an invaluable guide to the sweeping economic, social, and political changes that have remade life in the United States over the past twenty-five years. Levy tells a fascinating and insightful story about what happened to American Incomes and jobs. His plot resists the simple truths of everyday journalism, and explains the economic and political twists and turns that have shaped the current American economy - including the oil and food price inflations of the 1970s, the market deregulations and corporate downsizing of the 1980s, the emergence of women as sole breadwinners in many families, the migration of jobs to the suburbs, and the computerization of work. By making sense of these complex trends, The New Dollars and Dreams offers crucial insights into why, despite a thriving economy, many Americans no longer feel secure in their financial futures.